2022
DOI: 10.1080/10826084.2022.2129996
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Lower-Risk Cannabis Consumption from the Consumers’ Perspective: A Rapid Evidence Assessment

Abstract: In the current rapid evidence assessment, we summarize the existing research on lower-risk cannabis consumption as understood by those who consume cannabis. We identified 7111 unique articles published between 1900 and 2021 using search terms related to a) cannabis consumption, b) beliefs and behaviors, and c) positive outcomes. Twelve articles met our inclusion criteria. Three themes emerged that reflect lower-risk cannabis beliefs and behaviors (informed self-regulation, protective behavioral strategies, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Similar to other studies (Rotermann and Pagé 2018;Woodruff and Shillington 2016;Lin et al 2016), we also found that individuals who used cannabis as teenagers or young adults are more likely to self-medicate with cannabis. This could be attributed to a normalization of cannabis use in this population and a lower risk perception (St-Jean et al 2022), or it might be linked to cannabis dependence (Winters and Lee 2008). Moreover, medical cannabis use is more socially accepted than recreational use (Baumbusch and Sloan 2022), especially when prescribed by a health professional (Spilka et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other studies (Rotermann and Pagé 2018;Woodruff and Shillington 2016;Lin et al 2016), we also found that individuals who used cannabis as teenagers or young adults are more likely to self-medicate with cannabis. This could be attributed to a normalization of cannabis use in this population and a lower risk perception (St-Jean et al 2022), or it might be linked to cannabis dependence (Winters and Lee 2008). Moreover, medical cannabis use is more socially accepted than recreational use (Baumbusch and Sloan 2022), especially when prescribed by a health professional (Spilka et al 2019).…”
Section: Discussionmentioning
confidence: 99%